1995
DOI: 10.1192/bjp.166.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Religious Experience Within Mental Illness

Abstract: While conventional religious practice shows signs of decline, this does not necessarily imply a decline in religious belief. It comes as a surprise that psy chiatrists should be so reticent in their inquiry into this aspect of their patients' emotional and cognitive experience. Only 3% of a qualitative review of the total output of four major psychiatric journals between 1978-1982 contained a quantified religious variable, and only three out of 3777 articles scanned were centrally and quantitatively concerned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…Crossley, following up on Sims in the British Journal of Psychiatry in 1995, underscored both the clinical and research neglect of attending to religion and identified the steps that could be taken to address this neglect (Crossley, 1995). Despite these initial rumblings in the British journals mentioned here, we are not aware of training efforts that might begin to rectify the clinical and research oversights concerning patient spirituality.…”
Section: International Activitymentioning
confidence: 88%
“…Crossley, following up on Sims in the British Journal of Psychiatry in 1995, underscored both the clinical and research neglect of attending to religion and identified the steps that could be taken to address this neglect (Crossley, 1995). Despite these initial rumblings in the British journals mentioned here, we are not aware of training efforts that might begin to rectify the clinical and research oversights concerning patient spirituality.…”
Section: International Activitymentioning
confidence: 88%
“…Their knowledge of their patients' religious activities and the importance of religion in patients' lives was inaccurate: patients' group religious practices were correctly identified in half the cases, whereas individual religious practices were identified for only one-third. The reasons given by the clinicians in Trois-Rivières are the same as those given in Geneva ) and in the literature (Neeleman and Persaud 1995;Greenberg and Witztum 1991;Shafranske 1996;Lukoff et al 1995;Crossley 1995): they believe they lack the skills necessary to evaluate this dimension; they are afraid of weakening or provoking a relapse in the patient (''open door to madness''); they lack the time to investigate this dimension or they believe that it is not their job to do so but that of an almoner, church worker or other spiritual counsellor. During the study, several strategies were put forward by Quebec clinicians who worked with some very religious patients on a daily basis: cooperating with the patient's spiritual mentor to reduce the patient's resistance, examining the therapist's own religious attitudes to modify counter-transference feelings and, for the majority of them, acquiring knowledge of the patient's religion to better distinguish religious beliefs from delusion or obsessivecompulsive symptoms when interviewing patients.…”
Section: Clinicians Facing Patients' Religiositymentioning
confidence: 90%
“…Religious beliefs in psychiatric patients are relatively neglected by psychiatrists and psychologists [1][2][3]. This might be partly due to the fact that they are less religiously oriented than their patients and the general population [4,5].…”
Section: Introductionmentioning
confidence: 99%